Experiences with agricultural development in tropical Africa - De Wilde, John C.; World Bank. (Baltimore, Maryland. : The International Bank for Reconstruction and Development by the Johns Hopkins Press, 1967)
This book examines the way in which various interrelated aspects of the development of agriculture and animal husbandry have worked out in four specific areas: Nyeri District, Machakos District, Central Nyanza District and the Baringo and Elgeyo-Marakwet Districts
Volume 1
Includes bibliographical references and index
oo 22/10/18
Loans
Keywords: Agriculture